Triple-Layer Porous Transport Layers with Ultra-High Porosity for Enhanced Oxygen Transport and Catalyst Utilization in Water Electrolysis - Park, Seong Hyun; Park, Young Je; Jang, Seungsoo; Lee, Pilyoung; Yoon, Soobin; Park, Young‑June; Jung, Chi‑Young; Lee, Kang Taek (Nano-Micro Letters, 2025)
The commercialization of proton exchange membrane water electrolysis (PEMWE) for green hydrogen production hinges on the development of low-cost, high-performance titanium porous transport layers (PTLs). This study introduces a triple-layer Ti-PTL with a graded porous structure and a 75% ultra-high porosity backing layer, fabricated through tape casting and roll calendering. This triple-layer PTL, composed of a microporous layer, an interlayer, and a highly porous backing layer, enhances catalyst utilization, mechanical integrity, and mass transport. Digital twin technology using X-ray revealed increased contact area and triple-phase boundary at the interface with the catalyst layer, significantly improving oxygen evolution reaction kinetics. Numerical simulations demonstrated that the strategically designed porous structure of the triple-layer PTL facilitates efficient oxygen transport, mitigates oxygen accumulation, and improves reactant accessibility. Electrochemical evaluations showed improved performance, achieving 127 mV reduction in voltage at 2 A cm−2 compared to a commercial PTL, highlighting its potential to enhance PEMWE efficiency and cost-effectiveness. Highlights: 1 A novel triple-layer Ti-porous transport layer (PTL), fabricated using a practical and scalable tape casting and roll calendering process, enhances catalyst utilization by increasing interfacial contact area and the triple-phase boundary. 2 The ultra-high porosity (75%) backing layer and graded structure maximize oxygen transport, mitigate oxygen accumulation, and improve reactant accessibility. 3 Electrochemical evaluations demonstrate a 127 mV reduction in voltage at 2 A cm−2 compared to a commercial PTL, accelerating proton exchange membrane water electrolysis commercialization and supporting the transition to sustainable energy.